Interaction of ibuproxam with γ-cyclodextrin in solution and in solid state - J. M. Ginés; J. R. Moyano; M. J. Arias; J. I. Pérez-Martinez; A. M. Rabasco; P. Mura (ՀՀ ԳԱԱ հրատ.)
Interaction between ibuproxam (Ib)and y-cyclodextrin (γ-CD)was studied in liquid and solid states.In solution, complexation, to propose a model of the complexation mechanism in solution.
Keywords: Biology; Biochemistry; Pharmacology